2021
DOI: 10.1590/s0102-0536-20210210
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and phosphorus in spilanthol and phenolic compound yield in jambu plants

Abstract: Jambu has spilanthol and phenolic compounds that are responsible for several medicinal properties. Besides improving nutrient absorption, arbuscular mycorrhizal fungi (AMF) can change secondary metabolites’ yield. Thus, the aim of the current study was to evaluate AMF inoculation and P influence on shoot dry biomass yield, macronutrient content (N, P, K, Ca and Mg), total phenol contents and spilanthol percentage in jambu plants. The experiment followed a randomized block design at 3x4 factorial arrangement, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Medicinal active ingredients with single AMF inoculation had the higher effect size compared to that with multi-AMF inoculation. Differences in the species and combinations of AMF were thought to be an impact factor on the medicinal active ingredient in previous studies (Zeng et al, 2013b;Lima et al, 2017;Vieira et al, 2021). Similar to our result that Rhizophagus had the best effect on increasing the concentration of medicinal active ingredients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Medicinal active ingredients with single AMF inoculation had the higher effect size compared to that with multi-AMF inoculation. Differences in the species and combinations of AMF were thought to be an impact factor on the medicinal active ingredient in previous studies (Zeng et al, 2013b;Lima et al, 2017;Vieira et al, 2021). Similar to our result that Rhizophagus had the best effect on increasing the concentration of medicinal active ingredients.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, a large number of studies on AMF and medicinal plants have been conducted to explore the effects of mycorrhizal symbiosis on medicinal active ingredients (Zeng et al, 2013b;Ostadi et al, 2020;Duc et al, 2021;Zhao et al, 2022). Most studies found that AMF inoculation increased medicinal active ingredient contents in plants (Srivastava et al, 2016;Chen et al, 2017;Xie et al, 2018a), and a few researches reported AMF had negative or no effects on medicinal active ingredients (Vieira et al, 2021). The effects of AMF inoculation on medicinal active ingredients differed from organs (aboveground and belowground organs) and medicinal components (Zubek et al, 2012;Lima et al, 2017;Xie et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%